Changes in serum levels of perfluoroalkyl substances during a 10-year follow-up period in a large population-based cohort. (October 2016) - Stubleski, Jordan; Salihovic, Samira; Lind, Lars; Lind, P. Monica; van Bavel, Bert; Kärrman, Anna
Abstract: Poly- and perfluoroalkyl substances (PFASs) are a group of man-made fluorinated chemicals which have, at background levels, been associated with negative health effects in humans. Thus far, most human biomonitoring studies have evaluated the general change in PFAS concentration over time by continuously testing various individuals. This is one of the few studies to report the longitudinal trend of a range of PFAS concentrations in humans. In addition, this is the first known longitudinal study to include a large background level exposed cohort of both men and women with the same age and location who were repeatedly sampled from 2001 to 2014. The longitudinal change in concentration of eight PFASs detected in serum collected from the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) cohort were determined and compared to results from general population studies. The sex-dependent changes in PFAS concentrations over time were also assessed. Serum was sampled from the same individuals at ages 70 (collection period 2001–2004), 75 (2006–2009) and 80 (2011–2014, ). Eight (C6–11 ) of fourteen (C4–13 ) analyzed PFASs were usually detected in over 75% of individuals and assessed using a random effects (mixed) model. In the 579 individuals attending all three examinations, PFOSA and PFOS concentrations significantly decreased, while the remaining six PFASs significantly increased between ages 70 and 75. However, between ages 75 and 80 all PFAS concentrations significantly decreased. Overall from age 70 to 80, concentrations of PFHxS, PFUnDA, PFNA, and PFDA showed a significant increase (7% to 34%), whereas concentrations of PFOSA, PFHpA, PFOS, and PFOA (− 75% to − 27%) significantly decreased. Over time PFHxS concentrations increased more among women, while PFHpA concentrations showed a greater decrease among men. From age 70 to age 80, spanning from 2001‐2004 to 2011–2014, the PIVUS cohort showed decreases in circulating levels of some PFASs phased out of production with the exception of PFHxS and C> 8 PFASs. Contrary to other studies, PFHxS concentrations showed the greatest overall increase, which is likely attributed to a local drinking water contamination incident. Graphical abstract: Highlights: Longitudinal trends of 8 PFASs were determined in 579 participants repeatedly sampled from 2001-2014 at ages 70, 75 and 80. The detection rate was above 75% for most compounds over all three sampling periods. From ages 70 to 80, PFHxS, PFUnDA, PFNA and PFDA concentrations increased, while PFOSA, PFHpA, PFOS, and PFOA decreased. PFHpA concentrations decreased significantly faster and PFHxS concentrations significantly slower in men compared to women.